The genomics of prematurity in an era of more precise clinical phenotyping: A review. Issue 2 (April 2016) - Manuck, Tracy A.
Summary: Spontaneous preterm birth is a major public health problem, with a clear genetic component. Genetic association studies have evolved substantially in recent years, moving away from the traditional candidate gene analyses to newer approaches utilizing sophisticated analysis platforms to examine sequencing data, and shifting towards functional studies including methylation analysis. It is becoming increasingly evident that careful clinical phenotyping is crucial to high quality genetic association studies regardless of the assay or platform being used. Nonetheless, genetic studies of prematurity are hampered by numerous challenges including small sample sizes, incomplete phenotying, population stratification, and multiple comparisons. As the costs of sequencing and functional analyses continue to decrease, unbiased genome-wide assays will be more widely available. Researchers have met improved success recently when critically applying clinical phenotyping knowledge to group women prior to analyzing genotyping results. Eventually, as the analytic approaches evolve, it is likely that this methodology (combining precisely clinically phenotyped subjects with genome-wide data) will provide key information regarding the pathophysiology of prematurity, and provide potential new avenues for exploring innovative therapeutic strategies.